Patient-reported Outcomes Following Nonoperative Treatment of Pediatric First‐Time Patellar Dislocation - Soroush Baghdadi, MD; Steven Henick, MD; Edina Gjonbalaj, BS; Leila M. Alvandi, PhD; Eric Fornari, MD (Elsevier, 2024)
ABSTRACT: Background: Patellar instability is a common pediatric knee injury. The purpose of this study was to analyze patient-reported outcome measures (PROMs) after nonoperative treatment following a first-time pediatric patellar dislocation. Methods: In this single-center, retrospective study, patients <18 years old between January 2012 and December 2019 with a first-time patellar dislocation were evaluated. From this cohort, we included all those patients who initially underwent nonoperative management and followed up for at least 1 year. Measures of patellar height and patellofemoral dysplasia were collected. PROMs were collected at the initial and follow-up visit. Univariate and multivariate analyses were utilized to determine the rate and risk factors for recurrence and the changes in PROMs. Results: One hundred seventy-six knees were included in the initial analysis, and 80 in the pre- and post-PROM analysis. There was a 41% rate of recurrence at a mean of 16.4 months of follow-up. In a multivariate logistic regression model, trochlear dysplasia (OR: 4.53, 95% CI: 1.61-12.7, P = .004), patella alta (OR: 4.27, 95% CI: 1.76-10.3, P < .001), and tibial tubercle trochlear groove (TT-TG) >15 mm (OR: 2.49, 95% CI: 1.3-6.03, P < .001) were significant risk factors for recurrence. Patients with or without recurrence showed significant improvements in PROMs at 1 year follow-up. However, both groups had mean scores below the population average. Regardless of recurrence or not, Knee Injury and Osteoarthritis Outcome Score in Children Quality of Life scores ranked the lowest among all PROM scores at the final follow-up. Conclusions: The findings of this study provide further evidence of the high rate of recurrent instability and important associated risk factors to consider. We also found that despite the overall improvement in all PROM subscales 1 year following the initial episode, both recurrence and no-recurrence groups demonstrated lower mean PROM scores than normal values. Furthermore, quality of life subscales showed the smallest improvement among all patients. Our results may be used to counsel patients and families regarding expectations after first-time and recurrent patellar dislocations. Key Concepts: (1) Patellar instability is one of the most common pediatric sports injuries with a high risk of recurrence. (2) In the absence of other factors, a first-time patellar dislocation is generally treated nonoperatively, but the long-term outcomes are not clear. (3) In this study, we found a high risk of recurrent dislocation. In addition, while the patient-reported outcome measures improved for all patients, even patients without evidence of further instability demonstrated patient-reported outcomes lower than the general population. (4) Future research may reveal subtle residual instability or other factors as the reason for the lower functional status and also compare these outcomes with operative reconstruction. Level of Evidence: IV, Case Series